Sharpen the Students' Motivation through Reward toward English Learning - Mohamad Salik; Muhimatul Murtafi’ah; Ahadya Racmania; Sayyidatul Maghfiroh; Farhan Farhan (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2020)
A reward is an amusing and positive thing, it turns out that reward is very influential in increasing one's learning motivation, one's motivation is an unstable thing especially motivation to learn, sometimes strong but sometimes weak. In this study, researchers perceived students of 11th grade at MAN 1 Pasuruan, this observation carried out in 2 weeks and focusing on seeing the impact caused by giving rewards to students’ motivation, to make the data stronger, at the end of the teaching session, researcher conductedinterview session with 34 students related to the impact of providing rewards in increasing student motivation. For the result, almost all students in 11th grade at MAN 1 Pasuruan XI IIS 3 Classagree that rewards can increase learning motivation, and for the details, it will be explained in the following article.